(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Effective education in this context involves preparing students to explore and apply mathematical knowledge in various situations, providing a strong foundation for the development of intelligence and thinking skills. This research focuses on the challenges faced by 4th-grade students at SDN 4 Sukajaya in solving word problems related to multiplication of whole numbers. The object of this study is the students’ difficulty in understanding the concept of multiplication, while the subjects are 10 students who experience difficulties and a class teacher. The research method used is qualitative with a descriptive approach, aiming to provide a detailed account of the problems faced by students. The study found learning obstacles among 4th-grade students at SDN 4 Sukajaya in solving word problems involving the concept of multiplication of whole numbers. These obstacles include: 1) difficulty in understanding the problems, 2) difficulty in identifying mathematical concepts, and 3) difficulty in calculations. The contributing factors are: 1) internal factors, such as motivation, intelligence, behavior, attitude, and students’ physical condition (e.g., fatigue), and 2) external factors, such as facilities, teacher quality, and curriculum. Efforts to address these obstacles include: regular problem-solving practice, the use of varied and enjoyable teaching methods and media to boost motivation, and cooperation between teachers and students in monitoring learning progress